A replication of Ideological asymmetries and the determinants of politically motivated reasoning (2022) - Ryan Briggs; Michael J. Donnelly; Thomas Bergeron; Thomas Galipeau (Institute for Replication (I4R), 2023)
Guay and Johnston (2022) examine asymmetric politically motivated reasoning on the part of liberals and conservaites. In our replication of the paper we examine four potential issues with the analysis: confounding in the numeracy task, heterogeneity across ideological constraints, the use of control variables, and heterogenity in the moderator index items. None of these potential issues are in fact issues. The results are quite robust. We found only one minor issue with the codebook, which does not affect the results.
Keywords: 330